Determination of Organic Acids in Wine and Spirit Drinks by Fourier Transform Infrared (FT-IR) Spectroscopy - Regmi, Umesh; Rai, Krishna Prasad; Palma, Miguel (Journal of Food Science and Technology Nepal, 2014)
This study outlines the use of FTIR with partial least square (PLS) method and data obtained from the reference method is used to establish a full calibration model for tartaric acid, malic acid, lactic acid, succinic acid, citric acid and acetic acid using all matrix. It was not possible to obtain only one calibration for all analysed samples, but in some cases individual calibrations for specific samples were needed. It was due to the different matrixes in the studies samples: 12-15% ethanol (wines), 30-40% ethanol (spirits). Due to this reason, a calibration model was developed for each acid in red and white wine, and acetic acid in spirit drinks. During validation, strong correlation with the reference values and great accuracy were demonstrated for the higher concentration range (>0.6 g/L) in all acids while inferior result was obtained in low range (<0.6 g/L). But good result was obtained in lower concentration level both in wine and spirits in acetic acid, which explains that calibration and validation of the FTIR spectrometry depends very strongly on the composition of the sample set and on the quality of the reference analysis. The correlations for organic acids could further be improved with a more complete well distribution data base and optimizing wavelengths. DOI: http://dx.doi.org/10.3126/jfstn.v7i0.10564 J. Food Sci. Technol. Nepal, Vol. 7 (36-43), 2012